MENINGKATKAN KOMPETENSI AKHLAK SISWA MELALUI PROSES PEMBELAJARAN - Khairuddin Khairuddin (Jurnal Educative: Journal of Educational Studies, 2016)
Abstract The Realization noble nation generation is a the nation hope and also become a national educational practice purposes as specified in the Law of National Education System. Although the practice of education have been implemented to fulfill the above expectations, but the morals of the nation tend to degenerate even alarming, almost to the level of moral emergency . Such circumstances clearly require quickly and precisely revamping. The most and strategic populous of next generation is the primary school-age teenagers especially primary and secondary education students. From the perspective of learning, especially learning the value, the reformation need to be done without downplay what has been done before, as soon as possible and with the approach and the right strategy so that teenagers / students have moral competency. There are two approaches of the internalization of moral education in schools. First, moral education approach through the formal curriculum. Second, the approach of moral cultivation through the hidden curriculum. The hidden curriculum can be done with four strategies; normative, model, reward and punishment, and the learning environment. Theoretically and empirically, two learning approaches and four learning strategies can be used as an alternative to improve the morals through a learning process in schools. Keywords: decadence, moral, approach